Dificultades de traducción en los textos teatrales (Journal of the College of Languages (JCL), 2014)
The theatrical text is a literary genre is written to be represented on a stage. Present difficulties in translation because include elements paralinguistic, historical, social, cultural, etc. The drama contains dialect, slang, and jargon elements. Here the translator must decide in favor of a re-creation of such elements with dialects, slang, and jargon in the receiving. The main objective of this study presents a descriptive about the translation for the theater and the main problems in translation theatrical texts. Try to reach some conclusions about the following questions: What requires theatrical translation? and What is the perfect formation of the translator of theater texts?. The first part is an introduction to theatrical translation and the second part present the problems of translation of these texts, also the characteristics of the ideal translator of theatrical texts. In the second part of this study we have translated some phrases extracted from the drama "Three hats" of dramaturge spanish Miguel Mihura to translate into Arabic in order to explain the problems facing the translator theatrical.